2021
DOI: 10.1177/0020872820963425
|View full text |Cite
|
Sign up to set email alerts
|

Social exclusion, mental health, and social well-being among African immigrants in the United States

Abstract: This study examined the effects of social exclusion (socio-cultural and structural-economic exclusion) on the mental health and social well-being of African immigrants in the United States ( N = 409). We found that social exclusion increased depression and anxiety symptoms, decreased societal trust, increased subjective isolation, and increased worries about one’s safety among African immigrants. The results further indicated strong negative effects of discrimination on mental health and social well-being. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 40 publications
1
8
0
Order By: Relevance
“…It should be noted that the significant mediation effects of the social and environmental domain of acculturative stress, and not the attitudinal and familial acculturative stress, echo other studies that have shown interpersonal and structural exclusionary processes to have stronger impacts on immigrant wellbeing outcomes (Pascoe & Smart Richman, 2009; Saasa et al, 2021). To help explain this, some scholars have found cultural‐based variations in consequences of interpersonal rejection between collectivist and individualistic cultures.…”
Section: Discussionsupporting
confidence: 63%
See 2 more Smart Citations
“…It should be noted that the significant mediation effects of the social and environmental domain of acculturative stress, and not the attitudinal and familial acculturative stress, echo other studies that have shown interpersonal and structural exclusionary processes to have stronger impacts on immigrant wellbeing outcomes (Pascoe & Smart Richman, 2009; Saasa et al, 2021). To help explain this, some scholars have found cultural‐based variations in consequences of interpersonal rejection between collectivist and individualistic cultures.…”
Section: Discussionsupporting
confidence: 63%
“…Research evidence denotes that ethnic minorities and immigrants in the United States frequently face increased discrimination and social exclusion with negative implications for health and wellbeing (Carter et al, 2017; Davis et al, 2016; Saasa et al, 2021; Schmitt et al, 2014). Discrimination among minority groups has been linked to disproportionate rates of psychosomatic symptoms and negative mental health outcomes including depression, anxiety, and insomnia (Cheng et al, 2020; Davis et al, 2016; Kauff et al, 2017; Saasa et al, 2021) and adverse physical health outcomes such as chronic diseases and accelerated ageing (Priest & Williams, 2018; Simons et al, 2021). Conversely, the past few decades have seen increased research attention toward examining factors associating discrimination with negative health outcomes among historically disenfranchised US populations and other minority groups (Chen et al, 2021; Chen & Yang, 2014; Williams et al, 2019).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Empirical evidence indicates that several factors such as age, immigration status, religiosity, gender, education, and safety concerns can impact service utilization and help‐seeking among African immigrants (Adekeye et al, 2014; Akinsulure‐Smith et al, 2013; Chaumba, 2011; McCann et al, 2016; Orjiako & So, 2014). While sociocultural characteristics can influence underutilization, structural factors including social exclusion and limited opportunities for integration cannot be ignored in addressing mental health service use among African immigrants (Saasa et al, 2021; Viruell‐Fuentes, 2011). The sparse studies specifically addressing mental health service utilization among African immigrants in the United States have several limitations.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, different rates of acculturative stress may also place additional challenges on immigrant families, including responding to mental health and substance use problems (Adekeye et al, 2014; Covington‐Ward et al, 2018; McCann et al, 2016). Research also indicates that social exclusion, particularly cultural, structural, and economic dimensions of exclusion are significant predictors of mental health distress, isolation, and societal mistrust among African immigrants (Saasa et al, 2021). These factors can have implications for help‐seeking.…”
Section: Introductionmentioning
confidence: 99%